2020
DOI: 10.47723/kcmj.v16i2.268
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Diffusion Weighted MRI in the Detection and Localization of Prostate Cancer among a Sample of Iraqi Patients

Abstract: Background: Prostatic adenocarcinoma is the most widely recognized malignancy in men and the second cause of cancer-related mortality encountered in male patients after lung cancer. Aim of the study:  To assess the diagnostic value of diffusion weighted imaging (DWI) and its quantitative measurement, apparent diffusion coefficient (ADC), in the identification and localization of prostatic cancer compared with T2 weighted image sequence (T2WI). Type of the study: a prospective analytic study P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Studies [15,35,36], showed that camel milk has a high effect in inhibiting the growth and proliferation of HepG2 liver cancer cells and MCF7 breast cancer cells, they noted that camel milk has a high ability to kill programmed cells of HepG2 and MCF7 cells through the mechanisms of apoptosis and oxidative stress through the activation and stimulation of mRNA enzymes caspase-3 and programmed cell death receptors-4 (DR4), which leads to the inhibition of cancer cell proliferation and then their death. Camel milk has an inhibitory effect on HepG2 and MCF7 cells as well as an inhibitory role in HCT116 colorectal cancer and Eca109 esophageal cancer cells [37,38]. The results of Table (1) showed that β-CN degraders showed a high inhibitory effect against PC3 prostate cancer cells, when comparing the results of the rate of inhibition of β-CN degraders with normal HdFn cells, the rate of inhibition of cancer cells reached (12.…”
Section: Cytotoxicity Test Of β-Cn Proteolytic Against Three Types Of...mentioning
confidence: 97%
“…Studies [15,35,36], showed that camel milk has a high effect in inhibiting the growth and proliferation of HepG2 liver cancer cells and MCF7 breast cancer cells, they noted that camel milk has a high ability to kill programmed cells of HepG2 and MCF7 cells through the mechanisms of apoptosis and oxidative stress through the activation and stimulation of mRNA enzymes caspase-3 and programmed cell death receptors-4 (DR4), which leads to the inhibition of cancer cell proliferation and then their death. Camel milk has an inhibitory effect on HepG2 and MCF7 cells as well as an inhibitory role in HCT116 colorectal cancer and Eca109 esophageal cancer cells [37,38]. The results of Table (1) showed that β-CN degraders showed a high inhibitory effect against PC3 prostate cancer cells, when comparing the results of the rate of inhibition of β-CN degraders with normal HdFn cells, the rate of inhibition of cancer cells reached (12.…”
Section: Cytotoxicity Test Of β-Cn Proteolytic Against Three Types Of...mentioning
confidence: 97%